The Influence of Traditional Games on Freestyle Swimming Speed in Riau Aquatic Pekanbaru Swimming Association Athletes - Rezki Rezki; Sesi Melati; Fezyana Delsa Anugrah; Muhammad Ikhsan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
Increased swimming speed can be attributed to factors such as improved motor  coordination, physical endurance, and possibly other benefits gained through  traditional play. This study aims to evaluate the effect of participation in traditional games on increasing freestyle swimming speed in athletes who are members of the  Riau Aquatic Swimming Association in Pekanbaru. This study used an experimental  approach by dividing athletes into two groups: a group that underwent additional  traditional game sessions and a control group that underwent regular training  without additional intervention. Swimming speed measurements were carried out  before and after the intervention period. The results of the T test in table 4 for the  experimental group obtained a calculated T value = 29.665 > T table = 2.052 and a sig  value. (2.tailed) = 0.000 < 0.05. The conclusion of the research shows that traditional  games have a significant influence on freestyle swimming speed in athletes from the  Riau Aquatic Swimming Association, Pekanbaru, Riau Province.